Numerical Simulation Research on Layer-Crossing Directional Hydraulic Fracturing Technology - Zhou, Weilong (International Journal of Mechanical and Electrical Engineering, 2025)
This paper focuses on the prevention and control of coal and gas outbursts in high-gas, high-stress, and low-permeability coal seams. Through numerical simulation methods, the crack propagation mechanism and engineering application of cross-strata directional hydraulic fracturing technology are studied. Based on the RFPA (Rock Failure Process Analysis) system, a two-dimensional plane strain model is established to analyze the influence of in-situ stress, injection pressure, and coal seam gas pressure on the initiation and propagation of fractures. The research results show that the coal seam gas pressure significantly weakens the effect of high-pressure water injection. The higher the gas pressure, the greater the difficulty of coal body fracture and the higher the initiation pressure, and the injection pressure needs to be increased to optimize the fracturing effect. The directional hydraulic fracturing technology can effectively control the crack propagation along the preset path by arranging guide holes, forming a penetrating crack network, and avoiding the stress concentration and disordered crack problems caused by single-hole fracturing. The simulation shows that the directional fracturing technology has achieved the improvement of coal body pressure relief and gas drainage efficiency in the field application of Chengzhuang Mine, providing a safe and efficient permeability enhancement and pressure relief method for areas without protective layer mining conditions. This technology, by optimizing the crack direction and propagation behavior, has the dual advantages of improving oil and gas recovery efficiency and reducing environmental risks, and has significant engineering value for the development of unconventional reservoirs.